2015
DOI: 10.3906/vet-1310-47
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism identification and characterization ofGnRHR gene in Bos taurus and Bos indicus cattle

Abstract: The hypothalamic gonadotropin-releasing hormone receptor (GnRHR) plays an essential physiological role in reproductive function. In this investigation, we studied genetic variation in the entire coding region of GnRHR gene using PCR-SSCP technique in 250 Bos taurus (Holstein Friesian, Jersey) and Bos indicus (Malnad Gidda, Deoni) bulls. The genetic variants in GnRHR gene were determined by PCR-SSCP technique by using 5 sets of primers. SSCP analysis of fragment 1, comprising exon 1, and fragment 3, comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Though has not been studied yet in sheep, GnRHR gene polymorphism has been proven efficiency in association with reproductive performance in several breeds of goats, such as Chinese goats (An et al, 2009), Boer goats (Yang et al, 2011), Loashan dairy goats (Liu et al, 2014), and Shaanan goats (Li et al, 2011). Furthermore, high genetic variation of GnRHR has also been reported in both Holstein Friesian cattle and Malnad Gidda buffalos (Kerekoppa et al, 2015), and in Egyptian buffalos (Sosa et al, 2016). However, no previous study was conducted to describe the possible association of the GnRHR with growth traits of sheep to compare our results with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though has not been studied yet in sheep, GnRHR gene polymorphism has been proven efficiency in association with reproductive performance in several breeds of goats, such as Chinese goats (An et al, 2009), Boer goats (Yang et al, 2011), Loashan dairy goats (Liu et al, 2014), and Shaanan goats (Li et al, 2011). Furthermore, high genetic variation of GnRHR has also been reported in both Holstein Friesian cattle and Malnad Gidda buffalos (Kerekoppa et al, 2015), and in Egyptian buffalos (Sosa et al, 2016). However, no previous study was conducted to describe the possible association of the GnRHR with growth traits of sheep to compare our results with.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are accumulated pieces of evidence have increasingly been concerned with the importance of the GnRHR protein to act as a key element in the normal development of puberty (Zhang et al, 2018). Most mutations in GnRHR that either activate or inactivate their functions were reported to be responsible for several reproductive traits in domestic animals, such as cattle (Kerekoppa et al, 2015), buffalos (Sosa et al, 2016), and goats (Bemji et al, 2018). Thus, the investigation of single nucleotide polymorphisms (SNP) within this gene may be important to understand the possible causative SNP(s) behind a particular phenotypic trait.…”
Section: Introductionmentioning
confidence: 99%
“…Pattern I (AA),II (BB) and III (CC) entailed four, five and six bands, respectively. Likewise, Kerekoppa et al(2015) verified high genetic variation in GnRHR gene in cattle using PCR-SSCP technique, where fragment 1and 3 showed two patterns, fragment 2 and 4 exhibited three patterns and fragment 5 was monomorphic in bulls.…”
Section: Resultsmentioning
confidence: 53%
“…In pattern III, insertion was at position 4, deletion was at position 189, and the 3 nucleotides substitutions were at positions 204 (T/G), 206 (T/A) and 207 (A/T). In this respect, Kerekoppa et al (2015) reported high degree of genetic variation (14 SNPs) in the coding region of GnRHR gene among Holstein Friesian, Jersey, Malnad Gidda, and Deoni cattle. Also, Lirón et al (2011) characterized bovine GNRHR polymorphisms in beef bulls and found eight SNPs of which five in the coding regions, might at least part responsible for the differences within and among beef breeds in the time when bulls reach puberty.…”
Section: Resultsmentioning
confidence: 93%